Adverse Tissue Reactions and Metal Ion Behavior After Small‐Head Metasul Hip Arthroplasty: A Long‐Term Follow‐Up Study. Issue 2 (15th December 2021) - Ishida, Tsunehito; Tateiwa, Toshiyuki; Takahashi, Yasuhito; Nishikawa, Yohei; Shishido, Takaaki; Masaoka, Toshinori; Yamamoto, Kengo
Abstract : Objective: To investigate the long‐term survivorship, incidence of adverse reactions to metal debris (ARMD), and metal ion behavior in patients who underwent small‐head Metasul metal‐on‐metal (MoM) total hip arthroplasty (THA). Methods: Between February 1998 and September 2003, a retrospective study was performed on 43 consecutive patients (43 hips) who underwent unilateral cementless Metasul MoM THAs at our institution. Of them, 35 patients (nine males and 26 females) who were available for follow‐up more than 15 years after THA were enrolled in this study and underwent metal artifact reduction sequence magnetic resonance imaging (MARS‐MRI) to identify ARMD. The mean age at surgery of the patients was 59.7 years old (range, 31–83). Clinical and radiographic outcomes were evaluated retrospectively. Clinical examinations were conducted using the Harris Hip Score (HHS). Serum cobalt (Co) and chromium (Cr) ion levels and Co/Cr ratio were assessed at different postoperative periods of <5, 5–10, 11–14, and ≥15 years. Results: The mean follow‐up period for the 35 patients included was 18.1 years (range, 15–22). The mean HHS significantly improved from 44.6 ± 11.3 points preoperatively to 89.4 ± 7.9 points at the final follow‐up ( P < 0.0001). ARMD was found in 20% of the patients using MARS‐MRI. No signs of stem loosening were found clinically or radiographically, whereas cup loosening and ARMD were observed in three patients (9%), for whom revision THAs were performed. The Kaplan–Meier survival rates with revision for any reason as the endpoint were 90.9% at 5 years, 84.8% at 10 years, 84.8% at 15 years (95% CI, 67.1–93.6), and 70.3% at 20 years (95% CI, 43.6–87.0). The survival rates with revision for ARMD as the endpoint were 100% at 5 years, 96.6% at 10 years, 96.6% at 15 years (95% CI, 77.2–99.7), and 80.1% at 20 years (95% CI, 45.3–95.2). Serum Co ion level peaked at 5–10 years after THA, which was significantly higher than that <5 years; however, it decreased to the initial level after 15 years. In contrast, serum Cr ion level significantly increased at 5–10 years and then remained almost constant. Significant differences in Cr ion levels (1.0 vs 2.0 μg/L, P = 0.024) and Co/Cr ratio (1.3 vs 0.9, P = 0.037) were found between non‐ARMD and ARMD patients at >11 years postoperatively. Conclusion: Our results suggest that increased Cr ion levels and decreased Co/Cr ratio may be signs of ARMD in patients who underwent small‐head Metasul MoM THA. Abstract : This study examines the long‐term survivorship and incidence of adverse reactions to metal debris (ARMD) in patients who underwent small‐head Metasul metal‐on‐metal (MoM) THA and evaluates the diagnostic potential of serum metal ion levels in identifying ARMD. ARMD was found in 21% of patients. The rate of revision surgery due to ARMD increased rapidly from 4% to 20% between 15 and 20 years after THA, and the survival rate decreased from 84.8% to 70.3%. A difference in the long‐term in vivo behavior was observed between cobalt (Co) and chromium (Cr), and increased Cr ion levels and decreased Co/Cr ratio may be signs of ARMD in patients who underwent small‐head MoM THA